Frames [large type] : a Valentino mystery - Estleman, Loren D. (Estleman, Loren D. Valentino mystery., 2008)
Enter Valentino, a mild-mannered UCLA film archivist. In the surreal world of Hollywood filmdom truth is often stranger than celluloid fiction. When Valentino buys a decrepit movie palace and uncovers a skeleton in the secret Prohibition basement, he's not really surprised. But he's staggered by a second discovery: long-lost, priceless, reels of film: Erich von Stroheim's infamous Greed. The LAPD wants to take the reels as evidence, jeopardizing the precious old film. If Valentino wants to save his find, he has only one choice: solve the murder within 72 hours with the help of his mentor, the noted film scholar Broadhead, and Fanta, a feisty if slightly flaky young law student. Between a budding romance with a beautiful forensics investigator and visions of Von Stroheim's ghost, Valentino's madcap race to save the flick is as fast and frenetic as a classic screwball comedy. A quirky cast of characters, smart dialogue and a touch of romance make this Estleman's most engaging and accessible novel to date.